Fenologi Kelapa Sawit dan Hubunganya dengan Curah Hujan dan Kedalaman Muka Air di Lahan Gambut - Mubarok, Husni; Ahmad, Fendri; Tambusai, M Nizam; Hidayat, Agus Nur; Harahap, Imbransya Ali (Universitas Sebelas Maret, 2022)
Oil palm phenology is a period of developmental phases of oil palm which is used to determine the development of oil palm, especially flowers, and fruit. Research on oil palm phenology on peatlands provides an overview of proper peat management and high productivity. The study aimed to get information on the growth phase and the development of oil palm time on peat land and the correlation with the environmental factor. The method used was the Marihat variety which was planted in 2002 on peat land and relatively maintained for the water table at 40-60 cm. The research was conducted from August 2017 until December 2020 on one of the oil palm plantation companies in Siak Regency, Riau Province. Direct observations related to plants' vegetative and generative phases were carried out, which were observed on 24 plant samples every seven days. The results showed that the monthly oil palm frond leaf increase averaged 1,8 fronds. The time needed from the appearance of 1st frond until an unknown flower appeared on average is 218 days. The length of the male flower phase from the unknown flower to the dry male flower is an average of 78 days. The female flower phase period from unknown flowers until the oil palm fruits have harvested an average of 226 days. The time it takes for oil palms on peat soil, from the appearance of the 1st fronds to the fruits, to be harvested is an average of 444 days. The sex ratio of the flower is not correlated with the rainfall, the number of rainy days, and the water table because the water table on the location is always maintained. Optimizing the water table is essential for managing oil palm productivity on peatlands.